A new species of Aulacaspis Cockerell, 1893 (Hemiptera: Coccomorpha: Diaspididae) infesting cardamom from India - Joshi, Sunil; Mohammed, Nafeesa; Mendonce, Viyolla Pavana (Zootaxa, 2023)
A new species of scale insect in the genus Aulacaspis (Hemiptera: Coccomorpha: Diaspididae) is described and illustrated from Kerala, India. Aulacaspis elettaria Joshi & Nafeesa sp. n. was collected from the host plant Elettaria cardamomum (L.) Maton (Zingiberaceae). Biological notes on the species are provided, including information on the occurrence, spread and pest status of this species in Kerala. An identification key based on adult females is given to separate Indian species of Aulacaspis.